2020
DOI: 10.1182/blood.2019004161
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies rare variants in STAB2 associated with venous thromboembolic disease

Abstract: Deep vein thrombosis and pulmonary embolism, collectively defined as venous thromboembolism (VTE), are the third leading cause of cardiovascular death in the United States. Common genetic variants conferring increased varying degrees of VTE risk have been identified by genome-wide association studies (GWAS). Rare mutations in the anticoagulant genes PROC, PROS1 and SERPINC1 result in perinatal lethal thrombosis in homozygotes and markedly increased VTE risk in heterozygotes. However, currently described VTE va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 47 publications
7
49
1
Order By: Relevance
“…Cai et al [ 123 ], Mo et al [ 124 ], Sun et al [ 125 ], Martinelli et al [ 126 ], Zhao et al [ 127 ], Assimes et al [ 128 ] and Piechota et al [ 129 ] showed that CCR7, FCN1, ESM1, F8 (coagulation factor VIII), C1QTNF1, ALOX5 and MSR1 were an important target gene for coronary artery disease. STAB2 have been suggested to be associated with venous thromboembolic disease [ 130 ]. Genes such as COMP (cartilage oligomeric matrix protein) [ 131 ], CHI3L1 [ 132 ], PLA2G2A [ 133 ], P2RY12 [ 134 ], CR1 [ 135 ], HPSE (heparanase) [ 136 ], PTX3 [ 137 ] and SERPINE1 [ 138 ] were related to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al [ 123 ], Mo et al [ 124 ], Sun et al [ 125 ], Martinelli et al [ 126 ], Zhao et al [ 127 ], Assimes et al [ 128 ] and Piechota et al [ 129 ] showed that CCR7, FCN1, ESM1, F8 (coagulation factor VIII), C1QTNF1, ALOX5 and MSR1 were an important target gene for coronary artery disease. STAB2 have been suggested to be associated with venous thromboembolic disease [ 130 ]. Genes such as COMP (cartilage oligomeric matrix protein) [ 131 ], CHI3L1 [ 132 ], PLA2G2A [ 133 ], P2RY12 [ 134 ], CR1 [ 135 ], HPSE (heparanase) [ 136 ], PTX3 [ 137 ] and SERPINE1 [ 138 ] were related to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Importantly, and as highlighted in other parts of this review, interspecies conclusions should be made with caution, and despite the high level of homology between mouse and human VWFpp AA sequences (86%), plasma levels of VWFpp are not elevated in humans known to be heterozygous for loss-of-function stabilin-2 variants. 30 While we are only very recently learning about the details of how and where the VWFpp is cleared from the circulation, measurement of VWFpp levels in plasma has been used for several years as a biomarker of certain pathophysiologic states. Concomitant increases in VWFpp and mature VWF: Ag are found in situations of acute endothelial activation such as thrombotic thrombocytopenic purpura, hemolytic uremic syndrome, sepsis, and severe malaria.…”
Section: Clearance Of the Vwf Propeptide And Its Role As Biomarkermentioning
confidence: 99%
“…As a strategy to identify candidate variants that could explain the VTE phenotype in individuals with discordant class prediction, we first prioritized variants that were likely functional (stop loss/stop gain, frameshift, non-synonymous and splicing variants), located in known VTE associated genes (ABO, ARID4A, C4BPB, EIF5A, F2, F3, F5, F8, F9, F13A1, FGG, GRK5, MPHOSPH9, MAST2, NUGCC, OSMR, PLAT, PLCG2, PLEK1, PROC, PROS1, SCARA5, SERPINC1, SLC44A2, STAB2, STX10, STXBP5, THBD, TSPAN15, VWF) [56][57][58], that have not been reported or at a low frequency (<1‰) in public genomic data repositories (dbSNP, GnomAD) and that was present in only one of the sequenced patients. If no candidate variants was identified in known VTE genes, we extended our search to whole coding genes and also took into account the predicted deleteriousness of selected candidates using in silico tools such as SIFT, PolyPhen and CADD-v1.2 [59]…”
Section: Nmentioning
confidence: 99%